Operation of a modified anaerobic baffled reactor coupled with a membrane bioreactor for the treatment of municipal wastewater in Taiwan. Issue 10 (29th April 2019) - Sung, Hung-Nien; Katsou, Evina; Statiris, Evangelos; Anguilano, Lorna; Malamis, Simos
ABSTRACT: A modified anaerobic baffled reactor (ABR) combined with a submerged membrane bioreactor (MBR) was applied to treat municipal wastewater. The performance of this process was examined in terms of the removal of organic matter, suspended solids, turbidity and nitrogen. The raw wastewater was fed to the 105 L ABR and then the treated effluent was driven to a 58 L MBR equipped with a submerged hollow fibre ultrafiltration membrane module. The integrated modified ABR–MBR process resulted in the complete removal of total suspended solids (TSS) and in very high chemical oxygen demand (COD) removal (93.3 ± 3.8%). Furthermore, the recycling of mixed liquor from the MBR to the modified ABR resulted in some denitrification occurring in the first compartment of the ABR, resulting in 53 ± 6% removal of nitrogen by the integrated process. The membrane flux was stable and above 20 L/m 2 h. Membrane examination at the nanoscale indicated the deposition of small particles on the surface of the membranes.